Teacher-made Summative Test: An Analysis of Test Format, Index of Difficulty, Discrimination, and Distractors - Isabell Sengkaton; Muslih Hambali; Soni Mirizon (LINGUA: Jurnal Bahasa dan Sastra, 2020)
Abstract: This study was aimed at finding out the quality, index of difficulty, discriminating power, and effectiveness of distractors of teacher-made English summative test item format. The sample of this study was 44 eleventh-grade students of one public senior high school in Palembang. The data were collected from the result of the English summative test responded by eleventh-grade students of the school. The data were analyzed by using the table of multiple- choice test item format and item analysis. The result of the test item format showed that none of the item was in the good (accepted) category, 34 (85%) items were in the moderate category, and 6 (15%) items were in poor category. The result of index difficulty showed that 10 (25%) items were in difficult category, 12 (30%) items were in easy category, and 18 (45%) items were in satisfactory category. The result of discriminating power showed that 16 (40%) items had poor discriminating power, 10 (25%) items had moderate discriminating power, and 14 (35%) items had good discriminating power. The result of the effectiveness of distractors showed that from a total of 160 distractors 41% of them functioned effectively, 51% of the distractors functioned less effectively, and 8% of the distractors were ineffective. In short, the teacher- made English summative test of the eleventh-grade students of the school was not acceptable to be used as an instrument to evaluate the students’ English learning due to many aspects of a good test in terms of quality, index of difficulty, discrimination power and effectiveness of distractors were not fulfilled. Keywords: test item analysis, teacher-made summative test, English Abstrak: Studi ini bertujuan untuk mengetahui kualitas, indeks kesulitan, kekuatan pembeda, dan keefektipan pengecoh terhadap format butir tes sumatif Bahasa Inggris. Jumlah sampel sebanyak 44 siswa kelas 11 Sekolah Menengah Atas Negeri 3 Palembang. Data studi ini merupakan jawaban hasil sumatif tes yang dikerjakan oleh ke 44 siswa tersebut dan dianalisa menggunakan tabel format butir tes berbentuk pilihan ganda. Hasil format butir tes menunjukkan tidak satupun butir soal berkatagori bagus. Dari sejumlah 40 soal, 34 (85%) butir soal tergolong sedang dan sisanya 6 soal (15%) termasuk katagori kurang. Dari hasil indeks kesulitan butir soal terdapat 10 butir (25%) dianggap sulit, 12 butir (30%) mudah , dan 18 butir (45%) tergolong memuaskan. Untuk kekuatan pembeda, terdapat 16 butir (40%) soal kurang, 10 butir (25%) butir sedang, dan 14 butir (35%) dianggap bagus. Sementara itu, hasil keefektipan pengecoh menunjukkan 41% dari total 160 pengecoh efektif, 51% kurang efektif, dan 8% tidak efektif. Secara ringkas tes sumatif Bahasa Inggris buatan guru untuk kelas 11 kurang dapat diterima sebagai instrumen untuk mengevaluasi pembelajaran bahasa Inggris siswa dikarenakan terdapat beberapa aspek sebagai persyaratan tes yang bagus tidak sempurna terpenuhi. Kata-kata kunci: analisis butir tes, tes sumatif buatan guru, Bahasa Inggris